A tutoria nos cursos EAD no núcleo de educação a distância da Universidade Estadual do Oeste do Paraná: uma vereda em construção - Bassani, Luciane da Silva (2022)
The present study and research deals with the role of tutoring in the movements of the Distance Education (EaD) modality. Initially, we seek to trace a brief history of the presence of distance education in the world and, above all, in Brazil, in order to understand how this modality develops, as well as the importance of the teacher-tutor in this context, especially in attention to the process understood in the Nucleus. of Distance Education (NEaDUNI) of the Universidade Estadual do Oeste do Paraná, focusing on the Course of Letters - Portuguese Language and Brazilian Sign Language - Libras and Brazilian and Deaf Literature - Degree. The intention of this study is to carry out a survey on the profile of professionals involved in the teaching-learning process in distance education, aiming to contribute - from data analysis - so that the performance and involvement of tutors are guided from the philosophy of Rizoma , which guides the work carried out by NEaDUNI. Therefore, this work was woven from theoretical constructs and investigative lines, based on testimonies and documentary analysis of tutors and students of the Letras Libras course.